Pb Heavy Metal Content, Growth and Yield of Four Kale Varieties (Ipomea reptans Poir.) due to Dosage of Chicken Manure with Sediment Media of Sewers - Lia Amalia; Nunung Sondari; Budiasih; Tien Turmuktini; Elly Roosma Ria; Kovertina Rakhmi Indriana; Beni Komara (International Journal of Advanced Multidisciplinary, 2024)
Food insecurity is a condition in an area, community or household where the level of security and availability does not meet the standards needed for the growth and health of the majority of the population. Kangkung is a heavy metal-absorbing weed plant that many people like as a vegetable. Food security in urban communities is limited by existing land and growing media, so using media from sewer sediment is an alternative. The experiment used a factorial Randomized Block Design (RAK), consisting of two factors, namely the dose of chicken manure (A) with 4 levels as follows: a0 : 0 t ha-1 (control), a1 : 10 t ha-1, a2 : 20 t ha-1 and a3 : 30 t ha-1 and Kangkung Variety (K) with 4 levels as follows: k0 : Serimpi Variety, k1 : Amanda Variety, k2 : Bangkok LP-1 Variety and k3 : Bika Variety, so there are 16 treatment combinations repeated 2 times. The research findings indicated that there was no significant correlation between the dosage of chicken manure and the plant type in terms of plant growth, yield, and absorption of PB heavy metals, with the exception of leaf count. The optimum dose of chicken manure is 5.05 t ha-1 in the Serimpi variety with a maximum number of leaves of 11.30 plants-1, 5.27 t ha-1 in the Amanda variety produces a maximum number of leaves of 16.68 plants-1 , 9.20 t ha-1 in the Bangkok LP-1 variety produces a maximum number of leaves of 16.77 plants-1 and 3.83 t ha-1 in the Bika variety produces a maximum number of leaves of 18.66 plants-1.